2017
DOI: 10.1016/j.pep.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of tau protein and its frontotemporal dementia variants using a cleavable histidine tag

Abstract: Recombinant tau protein is widely used to study the biochemical, cellular and pathological aspects of tauopathies, including Alzheimer's disease and frontotemporal dementia with Parkinsonism linked to chromosome 17 (FTPD-17). Pure tau in high yield is a requirement for in vitro evaluation of the protein's physiological and toxic functions. However, the preparation of recombinant tau is complicated by the protein's propensity to aggregate and form truncation products, necessitating the use of multiple, time-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…As cysteine-291 is important for tau aggregation (Bhattacharya et al, 2001;Crowe et al, 2013;Soeda et al, 2015), we asked if the C291R mutation affects aggregation propensity. Each tau-K18 construct was mixed with a 50% mass concentration of heparin and incubated at 37 • C without shaking for 48 h. Negative-stain TEM analysis showed that tau-K18 WT aggregated into fibrils ( Figure 3A) in agreement with previous reports (Barghorn et al, 2000;Barghorn and Mandelkow, 2002;Karikari et al, 2017). These fibrils were 30-45 nm wide and 150-300 nm long.…”
Section: Tau-k18 C291r Aggregates Into Amorphous and Spherical Structsupporting
confidence: 88%
See 3 more Smart Citations
“…As cysteine-291 is important for tau aggregation (Bhattacharya et al, 2001;Crowe et al, 2013;Soeda et al, 2015), we asked if the C291R mutation affects aggregation propensity. Each tau-K18 construct was mixed with a 50% mass concentration of heparin and incubated at 37 • C without shaking for 48 h. Negative-stain TEM analysis showed that tau-K18 WT aggregated into fibrils ( Figure 3A) in agreement with previous reports (Barghorn et al, 2000;Barghorn and Mandelkow, 2002;Karikari et al, 2017). These fibrils were 30-45 nm wide and 150-300 nm long.…”
Section: Tau-k18 C291r Aggregates Into Amorphous and Spherical Structsupporting
confidence: 88%
“…We generated the pProEx-HTa-Myc-6 × His-K18 plasmid carrying the C291R mutation (TGT > CGT, the same codon change previously reported by Marshall et al, 2015) by site-directed mutagenesis using a WT tau-K18 plasmid as a template (Karikari et al, 2017(Karikari et al, , 2019a. Protein expression and purification were achieved using our previously-characterized recombinant tau production protocols (Karikari et al, 2017(Karikari et al, , 2019aHill et al, 2019). The purified His-tagged tau-K18 constructs were used directly in functional experiments since the His-tag does not appear to affect aggregation (Huseby et al, 2019).…”
Section: Cloning Protein Expression and Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of these toxic tau oligomers has been associated with mutations and overexpression of numerous chaperone proteins [36][37] , highlighting the importance of other components of the tau-protein interactome in the pathogenesis of tauopathies. Capturing this complexity in an in vitro setting is extremely difficult, if even possible, and established protocols for aggregating purified tau protein into oligomers, PHFs, and NFTs have, not surprisingly, been shown to produce different tau assemblies depending on aggregation conditions 17,31,34,[38][39][40][41] . Critically, no specific toxic tau species has been isolated or identified to date 21,[42][43] .…”
Section: Introductionmentioning
confidence: 99%